Gall Bladder Wall Thickness: Sonographic Accuracy and Laparoscopic Cholecystectomy Conversion Rate, Evaluated by Histopathology - Mohammad Faraj Dawod Al. Jafary1 , Ammar Fouad Abdulrazaq2 , Ayman Nadeem Kadum3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Preoperative prediction of a difficult laparoscopic cholecystectomy can help the patient as wellas the surgeon to prepare better for intraoperative risk and the risk of conversion to open Cholecystectomy.Aim of study: Evaluation the impact of gall bladder wall thickness, on the outcome of laparoscopiccholecystectomy and conversion rate to open cholecystectomy assessed by sonography preoperative andpostoperative measurement of gall bladder wall thickness by histopathology.Patients and Methods: A prospective study conducted in the surgical unit, Department of surgery, BaghdadTeaching Hospital between November 2010 and November 2011. Abdominal Sonography performed in 110consecutive patients before laparoscopic cholecystectomy. The surgeon re-verified sonographic finding inoperative room, and postoperatively, the gall bladder specimens were sent for histopathological measurementof wall thickness.Results: Out of 110 patients with cholecystolithiasis on sonography, we encountered easy laparoscopiccholecystectomy in 80 patients (72.7%), difficult laparoscopic cholecystectomy in 24 (21.8%) and theprocedure was converted to open cholecystectomy in six patients (5.5%). The difference between Sonographicand histological measurement was within 1 mm in 102 patients (92.7%), and the other 8 patients was with1.5 mm (7.3%) with sensitivity of (100%), specificity of (83.3%) and accuracy of (97%).Conclusion: An accurate preoperative diagnostic sonography is mandatory for planned laparoscopicgall bladder surgery to provide information for the selection of the most appropriate approach and avoidintraoperative difficulties and surprises. On sonography gall bladder wall thickening is the most sensitiveindicator of technical difficulties during laparoscopic cholecystectomy. Such difficulties may requireconversion to laparotomy.